Symbols and Sexual Perversion of Laura Wingfield in Tennesse Willimas’s The Glass Menagerie - Retnowati, Retnowati (Humaniora, 2015)
The Glass Menagerie, a play written by Tennessee Williams, is full of symbols in which some of them refer to the sexual perversion in the character of the play such as Laura Wingfield. The research applied library research by taking data from the script of the play, then analysed based on the two theories, those were the theory of symbol and psychological theory called sexual perversions. The symbols in this play was analyzed, especially those related to Laura Wingfield. There were symbols like the glass collection, glass unicorn, blue roses, fire escape and Jim O?Connor which explained the sexual perversion of Laura Wingfield. These symbols were clues to understand the psycological problems suffered by Laura. It can be concluded that The cause of the strange sexual desire is because of her being abnormal because she is crippled and suffers from pleurosis.